High impedance fault detection and identification based on pattern recognition of phase displacement computation - Ali, Mohd Syukri; Bakar, Ab Halim Abu; Tan, Chia Kwang; Arof, Hamzah; Mokhlis, Hazlie (Institute of Electrical Engineers of Japan, 2018)
This paper proposes a new algorithm for high-impedance-fault (HIF) detection based on phase displacement computation (PDC). The PDC is calculated between the measured and reference three-phase voltage signals. There are two stages in this algorithm. In the first stage, the pattern of the PDC is analyzed to detect the occurrence of an event. In the second stage, the peak of the PDC is used as a feature to distinguish between HIF and non-HIF events. Subsequently, an automatic HIF classification algorithm based on predefined indices is proposed to perform event identification and HIF detection. Different types of HIF events and non-HIF events, such as load switching, motor starting, and capacitor switching, have been simulated in PSCAD/EMTDC. The proposed algorithm is able to classify the events accurately for both single and multiple events occurrence.